Museum-university collaboration to renew mediation in art and historical heritage. The case of the Museo de Navarra - Arriaga, Amaia; Aguirre, Imanol (Arte, Individuo y Sociedad, 2020)
We present an action research project in which a university and a regional museum of art and historical heritage collaborate. The objective of this project has been to design and develop a mediation plan and its interpretation resources. First, a description is provided of the historical context of the debate regarding the educational function of the museum and mediation actions for the interpretation of art. Next, we present the theoretical principles on which our approach to mediation in museums is based and explain the two phases of the action research project. Initially, an investigation of the mediation tools offered by the museum is carried out. Next, a description is provided of how the conclusions drawn are materialized in the “All Art is Contemporary” project that renews part of the permanent exhibition and that offers accessible, rigorous, pluralistic and stimulating mediation/interpretation resources (gallery text, museum labels, etc.) that allow visitors to participate in the discourse that the museum proposes, turning it into a site of social interaction, a negotiation of meaning and an encounter between different sensibilities and identities. In short, it is a tool for continuous and critical civic education.